Knowledge transferring and small and medium enterprise's (SME's) effectiveness: emerging insights and future directions. Issue 6 (24th August 2021) - Biloslavo, Roberto; Lombardi, Rosa
Abstract : Purpose: This paper aims to define knowledge transfer and small and medium enterprise's (SME's) effectiveness. This research framework examines how employees understand, create and apply knowledge in a day-to-day working context, and how knowledge and other organisational factors influence knowledge transfer within the organisation. Design/methodology/approach: A qualitative research approach was applied. The authors conducted semi-structured group interviews with the members of three departments of a small hi-tech company. All collected data were manually coded, using in vivo coding and discussed among the authors. As the continuation of the semi-structured group interview, the technique of cognitive maps was applied. Findings: According to the results, the critical elements of knowledge transfer within small hi-tech companies seem (1) available slack time, (2) reciprocity and level of trust among employees, (3) social capital of employees and (4) practically oriented technical knowledge. It is also noted that the knowledge transfer is carried out to solve the problems identified by the employees, and these seek knowledge directly from the knowledge bearers who represent a kind of organisational memory. Practical implications: Knowledge transfer in SMEs occurs almost exclusively face-by-face, and individuals involved pay attention to the time required by this process. The co-creation of an organisational space that allows and supports an open discussion within and between departments is therefore of fundamental importance in order not to preclude organisational learning. In addition, non-financial incentives must be established to help transfer tacit knowledge. This allows to overcome the difficulty of employees in recognising the organisational knowledge base that they see above all in themselves. Originality/value: This paper throws additional light on understanding how knowledge transfer happens within small hi-tech companies. The applied qualitative research methods allow a better understanding of the "how" and "why" questions associated with the social processes surrounding knowledge transfer.